ANALISIS AIDA (ATTENTION, INTEREST, DESIRE, ACTION) TERHADAP EFEKTIVITAS IKLAN SEBAGAI DASAR STRATEGI PEMASYARAN ONLINE SHOP: Manajemen pemasaran - ENDANG NARYONO, SE., MM (P3M STIE PASIM Sukabumi, 2019)
This research is associative descriptive with the aim of this research is to explain the influence of factors from the concept of AIDA (attention, interest, desire, action), to determine the effect of AIDA on the effectiveness of online shop ads, and to explain the relationship of AIDA factors (Attention, Interest , Desire, Action) is the most dominant on the effectiveness of online shop advertising. The results of a study of 175 shoppers at online shop stores (Bukalapak, Lazada, Shop, Tokopedia, FThing, Purchasing) using factor analysis and multiple linear regression, the results obtained are four factors called interest, desire, action, attention . Based on the results of multiple linear regression analysis, partially the three factors of interest, desire, action have a significant effect or have a strong effect on the effectiveness of online shop advertising, while the attention factor does not have a strong or significant effect on the effectiveness of online shop advertising, and attention, interest, desire, action have an effect significantly based on joint testing. Interest is the dominant factor influencing online advertising.